Sustainability evaluation of sugarcane bagasse valorization alternatives in valle del cauca - Colombia (2018)
In the present paper, an evaluation methodology of the sustainability was proposed in order to select the best way to value the sugarcane bagasse, taking into account the environmental management of the process, economic indexes, and social relevant aspects. To evaluate the environmental dimension, the Life Cycle Assessment (LCA) methodology and the LCA specialized software SIMAPRO was used. Six Impact categories were evaluated: acidification (Kg eq SO2), eutrophication (Kg eq PO4), climatic change (Kg eq CO2), photochemical oxidation (Kg eq C2H4), ozone layer depletion (Kg eq CFC-11) and abiotic damage (Kg eq Sb). It was found that in the case of co-generation use of sugarcane bagasse, the unitary process that generates greater environmental impact is the boiler and in the case of paper production, it’s the pulp bleaching. The economic dimension was evaluated using the Life Cycle Cost (LCC) methodology. This methodology analyzes the economic aspects through the life cycle of the sugar cane bagasse. The Internal Rate of Return (IRR) was selected as the economic indicator, the value obtained for this indicator for the cogeneration process was 0,355 and for the paper production process 1,816. Both results show economic cost-effectiveness. A stakeholder analysis was made in order to evaluate the social dimension. For each process, the power and interest criteria were evaluated. It was found that in the process of cogeneration, power and interest levels are 4 and 5,4 out of 10 respectively, and in the process of paper, power level was 3,1 and interest 5,2 out of 10. Finally, the results of the three dimensions were integrated using the Analytical Hierarchy Process methodology (AHP): Environmental dimension obtained with LCA, Economic dimension evaluated with LCC and social dimension calculated with stakeholder analysis. The main conclusion is that the most sustainable use of sugarcane bagasse is the raw material in the paper industry. Some sustainability recommendations were given for both processes evaluated. Copyright © 2018, AIDIC Servizi S.r.l.